2006
DOI: 10.1002/adem.200600100
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Development of a New Iron Age

Abstract: Steel in its various forms is the most widely utilized metallic alloy and comprises over 80 % by weight of all metallic alloys in industrial use.[1] The development of steel microstructures is based on manipulation of a very specific solid/solid state transformation called an eutectoid transformation (i.e. γaustenite → αferrite+ Fe3Ccementite). The control of this transformation is the primary factor resulting in wide variety of microstructures and resulting properties found in commercial steel alloys. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…have been used to create amorphous coatings in which the BMG particles/powders undergo significant deformation as well as thermal hysteresis. [6] Therefore, the thermal stability and effects of changes in test temperature on the flow behavior are vitally important to both the processing and subsequent properties of these coatings.…”
Section: Introductionmentioning
confidence: 99%
“…have been used to create amorphous coatings in which the BMG particles/powders undergo significant deformation as well as thermal hysteresis. [6] Therefore, the thermal stability and effects of changes in test temperature on the flow behavior are vitally important to both the processing and subsequent properties of these coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Several Fe-based structural amorphous metal ͑SAM͒ compositions have been developed. [8][9][10][11][12][13][14][15][16][17][18] Farmer et al reported an Fe-based BMG with a nominal composition of Fe 48 Cr 15 Mo 14 C 15 B 6 Y 2 ͑SAM 1651͒ having a high corrosion resistance in hot, concentrated calcium brine. 8 Shan et al investigated the corrosion behavior of SAM 1651 and crystalline Ni-based alloy 22 in hot concentrated brine and showed that SAM 1651 was more corrosion resistant than alloy 22 at high oxidizing potentials.…”
mentioning
confidence: 99%
“…5 Recently, we have reported a specific structure type called a SGMM structure, which has the ability to deform without runaway shear propagation resulting in the achievement of significant levels of global plasticity and usable ductility. [21][22][23][24] The structural formation model for the SGMM structure required for monolithic technology is shown in Fig. 5.…”
Section: Monolithic Technologymentioning
confidence: 99%
“…Two types of interactions are observed, which are called induced shear band blunting (small circles) and shear band arresting interactions (SBAI) (large circles). [21][22][23][24] In Fig. 6b, additional details of the induced shear band blunting process are shown as a propagating shear band is interacting with the SGMM structure and is blunted due to complex multifold interactions of the shear band with the SGMM structure through localised deformation induced changes including phase transformation, phase growth and in situ nanocrystallisation.…”
Section: Monolithic Technologymentioning
confidence: 99%
See 1 more Smart Citation